FORMATION OF EMOTIONAL INTELLIGENCE IN PRESCHOOL CHILDREN BASED ON GAME TECHNOLOGIES - Badriddinova Firdavskhon Husniddin kizi (International Journal of Literature and Language Studies, 2026)
The article analyzes the pedagogical potential of game technologies in the formation of emotional intelligence in preschool children. The study is based on the four-branch theoretical model of emotional intelligence developed by Mayer and Salovey, as well as on pedagogical and psychological views on the leading activity of the child in play. The purpose of the study is to determine the impact of didactic, plot-role-playing and action games on the skills of recognizing, expressing, understanding and managing emotions in children, as well as to assess the practical training of educators in this regard. The study used pedagogical experimental-testing, observation and questionnaire methods. The results showed that purposefully organized plot-role-playing games and didactic games reflecting emotions expand the emotional vocabulary of children, develop empathy and self-management skills, but this effect is stable only in the presence of conscious pedagogical intervention (scaffolding) of the educator. The article concludes with practical recommendations for the systematic use of gaming technologies to develop emotional intelligence.